MEKANISME LEGISLATIVE REVIEW PERATURAN PEMERINTAH PENGGANTI UNDANG-UNDANG DALAM PERSPEKTIF POLITIK HUKUM - Efendi, Muhammad Fadli (Veritas et Justitia, 2021)
With the issuance of Constitutional Court decision No. 138/PUU-VII/2009, a legal conflict arises between the Parliament and Constitutional Court, regarding which state institution possess the authority to review any Government Regulation in lieu of Law.  Both institutions declared themselves to be having the sole authority to do just that.  The author, using a juridical normative approach, suggest otherwise. In the auhtor’s opinion, it is the Parliament who should be regarded as having the sole authority. This said taking into consideration that – as soon as the emergency justifung the issuance of the government regulation in lieu of legislation ends – both the government and the parliament shall as soon as possible convene to determine whether this government regulation should be declared null and void or elevated to the status of Law.